PERAN PEMUDA DALAM PENYELENGGARAAN PEMERINTAH DESA - Syarwan, Muh; Rahman, Budiarti (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2024)
This research aims to analyze the role of youth in village government administration. The problem raised was related to the implementation of the Village Head’s authority which was considered less open so that community participation, especially youth, was not involved in decision-making areas and missed out on information related to the programs being implemented. This research is qualitative research with a normative syar’i and juridical theology approach. Data collection methods were carried out by means of interviews, observation and documentation. The results of research on the role of youth in the administration of Village government show that Village government is less open and does not involve youth in decision making in Village development deliberations, resulting in low representation of youth needs and aspirations resulting in an imbalance in village development planning with less focus on youth initiatives. and the potential contribution of youth. Lack of youth participation also has an impact on low motivation to get involved in village development projects which results in a lack of encouragement to create innovative solutions to local problems so that it has long-term impacts and is detrimental to the sustainable development of the village as a whole.